889Association of maternal smoking during pregnancy and early-childhood with adult insomnia symptoms. (2nd September 2021) - Melaku, Yohannes Adama; Appleton, Sarah; Reynolds, Amy; Gill, Tiffany; Sweetman, Alexander M; Micic, Gorica; Stevens, David J; Lack, Leon; Adams, Robert
Abstract: Background: Evidence regarding the association between perinatal smoking and insomnia symptoms in adulthood is limited. Using the UK 1970 Birth Cohort Study, we determined the association of maternal smoking during pregnancy and early-childhood with insomnia symptoms at 42 years. Methods: Participants were followed from birth (1970; N = 9020; male, 48%) and age 5 (1975; N = 8050; male, 47.9%) to 42 years (2012). Data on maternal smoking was collected at birth and age 5; difficulties initiating or maintaining sleep (DIMS) and DIMS plus daytime symptoms (tiredness, irritability, depression and nervousness) [DIMS plus] at age 42. We used a direct acyclic graph to select confounders. A log-binomial logistic regression, adjusted for confounders, was used to estimate the association. Missing data were imputed via multiple imputation. Results: The prevalence of DIMS and DIMS plus was 32% and 25%, respectively. There was a 25% [odds ratio (OR)=1.25; 95% confidence interval (CI): 1.12-1.38)] and 23% [OR = 1.23; 95% CI: 1.09-1.38] increase in odds of DIMS and DIMS plus among participants whose mothers smoked during pregnancy compared to those whose mother did not. A 24% [OR = 1.24; 95% CI: 1.12-1.37] and 18% [OR = 1.18; 95% CI: 1.05-1.33] increase in odds of DIMS and DIMS plus respectively, was observed among participants who had smoking mothers at age 5. Intensity and duration of smoking had a dose-response relationship with insomnia symptoms. Conclusions: Maternal smoking during pregnancy and early-childhood is associated with increased risk of adult insomnia symptoms. Key messages: This study suggests that reducing maternal smoking may reduce the risk of adult insomnia.